Becoming - Obama, Michelle 1964- (New York Crown, 2018)
Michelle Obama describes her triumphs and her disappointments, both public and private in a deeply personal reckoning of a woman of soul and substance who has steadily defied expectations.
Becoming me -- Becoming us -- Becoming more.
Keywords: Obama, Michelle, -- 1964-; Presidents' spouses -- Biography -- United States; African American women lawyers -- Biography -- Illinois; African American women -- Biography; Legislators' spouses -- Biography -- United States; Autobiographies